2019
DOI: 10.1021/acs.est.9b01131
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the Fate and Removal of Antibiotics in Engineered Biological Treatment Systems: A Critical Review

Abstract: Antibiotics, the most frequently prescribed drugs of modern medicine, are extensively used for both human and veterinary applications. Antibiotics from different wastewater sources (e.g., municipal, hospitals, animal production, and pharmaceutical industries) ultimately are discharged into wastewater treatment plants. Sorption and biodegradation are the two major removal pathways of antibiotics during biological wastewater treatment processes. This review provides the fundamental insights into sorption mechani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
211
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 734 publications
(211 citation statements)
references
References 426 publications
0
211
0
Order By: Relevance
“…High concentrations of individual antibiotics up to several μg/L were also detected in other E-STPs in the world, e.g. 0.011-8.3, 0.001-1.8, and 0.024-6.8 μg/L for SMX, TMP, and OFL, respectively 9 . SAs, QNs, and MLs were also frequently detected in STPs worldwide 27 .…”
Section: Antibiotic Concentrations In E-stpsmentioning
confidence: 89%
See 2 more Smart Citations
“…High concentrations of individual antibiotics up to several μg/L were also detected in other E-STPs in the world, e.g. 0.011-8.3, 0.001-1.8, and 0.024-6.8 μg/L for SMX, TMP, and OFL, respectively 9 . SAs, QNs, and MLs were also frequently detected in STPs worldwide 27 .…”
Section: Antibiotic Concentrations In E-stpsmentioning
confidence: 89%
“…The high population density in cities lead to large consumption and emission of antibiotics. Sewage, hospitals, livestock and poultry farms, and aquaculture are important pollution sources of antibiotics 9 . Besides domestic sewage, industrial and hospital wastewater are also discharged into sewage treatment plants (STPs) 10 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another review article focused on sorption and biodegradation pathways of various antibiotics in engineered biological wastewater treatment systems (Oberoi, Jia, Zhang, Khanal, & Lu, 2019). Authors concluded that redox conditions influenced the abundance and distribution of microbial communities and sorption and biodegradation mechanisms.…”
Section: Pharmaceuticals Antibiotic‐resistant Bacteria and Antibiotmentioning
confidence: 99%
“…Antibiotics are widely used as the specific drug for treating bacterial infection in humans and animals, while the abuse of antibiotics has caused the high levels of antibiotic residues in surface and groundwater as well as in drinking water [1][2][3]. Owing to the antibiotic wastewaters being highly poisonous and difficult to degrade, monitoring of antibiotic wastewaters was significant, but challenging [4,5]. Compared with the traditional detection method of antibiotics using instrumental methods such as liquid chromatography (LC), capillary electrophoresis (CE), liquid chromatography mass spectrometry (LC-MS), Raman spectroscopy (RS), ion mobility spectrometry (IMS), and so forth, the metal organic frameworks (MOFs) used as luminescent probes for the selective detection of antibiotics has been considered as a very effective and proven technology [6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%